Cardiovascular effect of testosterone replacement therapy in aging male - Francomano, Davide; Bruzziches, Roberto; Natali, Marco; Aversa, Antonio; Spera, Giovanni (Acta Biomedica Atenei Parmensis, 2010)
Cardiovascular diseases (CVD) are the most important causes of morbidity and mortality in the developed and developing world. Particularly, coronary heart disease is the commonest cause of death worldwide. Testosterone (T) is an anabolic hormone with putative beneficial effects on men’s health and restoration of normal T levels in deficient men represents an important key-point of male well-being. In the lasts years it has emerged a possible linkage between androgen deficiency and CVD. Many studies noted that T deficiency might contribute to increased risk of CVD. Furthermore, androgen deficiency is frequently associated with increased levels of glucose, total cholesterol, low-density lipoprotein, increased production of pro-inflammatory cytokines, and increased thickness of the arterial wall that all contribute to worsen endothelial function. The clinical and epidemiological studies discussed in this section give an update on the interplay between late onset hypogonadism (LOH) and CVD. The linkage between androgen deficiency and men’s vascular health has a great impact in the modern approach to the ageing male, and should be further investigated to determine the therapeutic potential of androgens in men with vascular disease.